Assessment of IL-10 and TGF-β1 among Patients with Celiac Disease - Jassim, Al Fadhl Hassanein Khalil; Ali, Angham Jasim Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Celiac disease (CD), also known as "celiac sprue," is a persistent inflammatory condition that involves the small intestine, with a incidence of 1% in the majority of population. This study aimed to investigate the role of some immune parameters such interlukin-10 (IL- 10) and Transforming growth factor-beta1 (TGF-β1) among patients with Celiac Disease. This study was conducted on a total of (75) individual in different sex and age group cases (26 males + 49 females) including (30) patients with Celiac Disease and (15) on a Gluten free diet and(30) healthy individuals. CD patients were recruited at Imam Sadiq Teaching Hospital, through the duration of the beginning of August 2019 till the end of December 2019. All patients diagnosed with CD by Anti-tTG test. The age range of the study population was from (5-75) years with mean age 32 years. Blood was withdrawn from a vein, for hematology analyzer (total WBCs count, total RBCs count and ESR) the serum was used for immunological tests including IL-10 and TGF-β1 by ELISA technique. The findings revealed that the total WBCs count and ESR were elevated significantly (p< 0.01) in CD patients as (mean= 11.56),(mean= 91) receptively, and CD patients had a significantly lower mean RBC count than healthy Group , 4.39 vs. 4.81 x103 cell/ml, respectively (p=0.01). GFD group had a significantly lower mean RBC count than healthy Group 4.49 vs. 4.81 103 cell/ml, respectively (p=0.01). Celiac Disease patients had a significantly higher mean of IL-10 than the healthy Group, 443.34 vs. 244.87, respectively. (P. value